PENYULUHAN TENTANG PERILAKU HIDUP BERSIH DAN SEHAT PADA ANAK USIA SEKOLAH DENGAN METODE EDUKATIF INTERAKTIF - Joni Siagian; Amelia Dini Anggraini Silalahi; Khairunnisa Batubara; Febi Annisa Lubis; Isbatul Khoiroh; Nasywa Azra Zeina Sirait; Tia Ariska Panjaitan (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2025)
Clean and Healthy Living Behavior (PHBS) is one of the effective preventive efforts in improving the health of the community, especially school-age children. Children are an age group that is vulnerable to various diseases due to lack of knowledge and good hygiene practices. This community service activity was carried out at Kinder Star Elementary School with the aim of improving the understanding and practice of PHBS among elementary school students. The activity methods include interactive counseling, demonstration of hand washing practices, and evaluation of student understanding through pre-tests and post-tests. The results of the activity showed a significant increase in student knowledge and skills related to PHBS. The discussion focused on the importance of integrating health education into the basic curriculum and the involvement of teachers and parents. This activity has a positive impact on increasing children's health awareness from an early age and is expected to be a model for similar activities in other schools.